Hydration characteristics of cement with high volume circulating fluidized bed fly ash. (30th May 2023) - Zheng, Dapeng; Wang, Dongmin; Cui, Hongzhi; Chen, Xiangsheng
Highlights: Ultrafine grinding can destroy the core–shell structure of f -CaO and II-CaSO4 . Physical activation can accelerate the mutual excitation of CFBFA and cement. The later strength of cement with 50% UCFBFA can reach the level of pure cement. The hydration mechanisms of cement with three types fly ash were discussed. Abstract: Circulating fluidized bed fly ash (CFBFA) is a large industrial solid waste generated by clean circulating fluidized bed coal combustion technology. The coarse and porous particle structure and high content of f -CaO and II-CaSO4 are the main obstacles to the wide application of CFBFA as a supplementary cementitious material. In this study, the core–shell structure of f -CaO and II-CaSO4 were destroyed, and the pozzolanic activity of CFBFA was enhanced by ultrafine grinding. Physical activation can accelerate the mutual excitation of CFBFA and cement, promote the formation of ettringite (AFt) in the early stage of hydration, improve the microstructure, and the later strength of cement with 50 wt% UCFBFA can reach the level of pure cement. The hydration mechanisms of cements with pulverized fuel ash (PFA), CFBFA and ultrafine CFBFA (UCFBFA) were also comparatively analyzed and discussed. This study proves that ultra-fine grinding can effectively improve the reactivity of CFBFA, which provides ideas for the future research on the stability improvement of CFBFA-based cement and the large-scale resource application of CFBFA.